CFD Simulation of Flow and Mass Transfer in Structured Packing Distillation Columns - 陈江波 刘春江 袁希钢 余国琮 (Chinese journal of chemical engineering, 2009)
Detailed investigation of flow behavior in structured packing distillation columns is of great importance in accurate prediction of process efficiency and development of more efficient and optimal equipment internals. In this study, a three-dimensional two-phase flow model based on VOF method for simulating the hydrodynamics and mass-transfer behavior in a typical representative unit of the structured packing is developed. In the proposed model, the c 2 - ε c model is used for the closure of turbulent mass transfer equation. By solving the proposed model, the velocity distribution, phase fraction profile and concentration field are obtained. Using these data, the total liquid holdup, the wetted area and the separation efficiency [height equivalent to a theoretical plate （HETP）] are estimated. For testing the model validation, the simulated HETPs are compared with our previous experimental data obtained in a 150 mm-diameter column containing Mellapak 350Y operating at the pressures of 0.6-1.8 MPa. The compari-son shows that they are in satisfactory agreement, with an average absolute deviation （AAD） of 25.4%.